Imperatives of in-service training and staff development in Indian forest service - Ray, P.N. (1995)
"To realise goals of National Forest Policy (1988), while induction training has been adequately revitalised, the in-service training has suffered negligence, according to the author. He, therefore, focuses on the need for its improvement and argues for creation of a Staff College for IFS"
Keywords: Civil service - India; Civil service - Training of; Civil service